Teacher Involvement in Introducing Beginning Mathematical Concepts to Early Childhood - Fitri Laelatul Mar'ah; Atania Karima; Lusi Dwi Shakira; Alifia Sekar Kinasih; Lathipah Hasanah (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2022)
This study aims to determine the involvement of teachers in introducing beginning mathematics to early childhood. This study uses a descriptive qualitative approach. The data collection technique was carried out using structured interviews with research subjects involving 5 Early Childhood Education (PAUD) teachers in the South Tangerang area who were selected through purposive sampling. Data analysis in this study uses the concept of Miles and Huberman, namely data analysis, data reduction, data presentation and conclusion. The results of the interviews were analyzed to find out the media, methods, constraints, solutions and children's responses to the introduction of early mathematics. The results obtained in this study indicate that teachers play an important role in introducing early childhood math classes which can be done in various ways according to the needs of each child. The introduction of early math concepts to early childhood involves teachers taking an important role in banning children from PAUD. The existence of use of learning media, methods and strategies that are very diverse so that teachers are expected to be able to help children introduce mathematics to early childhood.